Male bull-headed shrikes use food caches to improve their condition-dependent song performance and pairing success. (June 2019) - Nishida, Yuusuke; Takagi, Masaoki
Abstract : Food caching is common in many animal species and is thought to have evolved largely by natural selection. We propose that sexual selection also plays an important role in the evolution of food caching. The sexual trait promotion (STP) hypothesis predicts that if male food caches provide supplemental nutrition allowing males to improve their sexual traits (e.g. song) serving a role in female choice, then sexual selection would act on male food caching. To test this idea, we investigated correlations between the number of caches that males retrieved, male song and pairing success, in the bull-headed shrike, Lanius bucephalus . Our field observations showed that the number of food caches males retrieved was positively correlated with male singing tempo (i.e. the number of notes uttered per second), not with other song characteristics (e.g. repertoire size). The bull-headed shrike's singing tempo has been found to reflect the nutritional condition of the singer and females choose their mates based on the tempo. Food supplementation experiments showed that males with artificially augmented food caches sang at higher speeds and mated with females earlier than controls; conversely, cache removal experiments showed that males with depleted food caches sang at lower speeds and were more likely to fail to mate than controls. Our results suggest that the food caches of male bull-headed shrikes provide them with supplementary nutrition allowing them to improve a condition-dependent song characteristic, which in turn serves the function of female attraction. We therefore conclude that sexual selection is an important evolutionary force acting on male food caching. Highlights: Male bull-headed shrikes stored food in their territories during autumn and winter. Males retrieved most of the food caches before the breeding season commenced. Males that retrieved more food caches sang more attractive songs to females. Males whose food caches were artificially augmented sang more attractive songs. Males whose food caches were artificially removed sang less attractive songs.